PENINGKATAN KERAGAMAN GENETIK MAWAR MINI MELALUI KULTURIN-VITRO DAN IRADIASI SINAR GAMMA - Wahyu Handayati; Darliah Darliah; I Mariska; R Purnamaningsih (Research Center for Biology-Indonesian Institute of Sciences, 2001)
Mini rose (Rosa hybrida L.)is one of the favorite ornamental plants. To get a new appearance of this mini rose, two experiments were conducted at Cipanas and Bogor, from April 1999 to March 2000.In the first experiment, the treatment was the dosage of gamma ray irradiation, i.e. 0, 1, 2, 3, 4, 6, 8, 10 and 12 krad.In the second experiment, the treatment was the concentration of callus induced mediumi.e. 2,4-dichlorophenoxyacetic acid (2,4-D) (0.5 and 1 mg/1) + chinetine (1, 3 and 5 mg/1).Randomized Block Design was used with 5 replications. Mini rose Romantica Meilandina (pink color) and Prince Meilandina (dark red color) was used as a source of plant material.The results showed that the irradiation dosage from 1 until 3 krad gave the best appearance compared with the other treatments.Considering the observance to plantlet in the same dosage, the color of the flower was changed from the natural color to white and red color.The combination of 0,5 mg/12,4- dichlorophenoxyacetic acid + 3 mg/1 chinetine was the best medium to the callus growth.